Measuring the Social and Economic Impact of Community Engagement Projects: A Framework for Sustainable Outcomes - Muhammad Fikri Fahrialdie (LPPM Akademi Teknik Adikarya, 2025)
Community engagement projects play a pivotal role in fostering inclusive and sustainable development, yet their social and economic impacts are often difficult to quantify systematically. This study aims to develop a comprehensive framework for measuring the multidimensional impacts of community engagement initiatives, integrating both qualitative and quantitative indicators. Using a mixed-methods approach, data were collected from various community development programs across urban and rural areas through surveys, interviews, and focus group discussions. The proposed framework evaluates four key dimensions: social capital enhancement, economic empowerment, participatory governance, and long-term sustainability. Findings reveal that projects emphasizing co-creation, local ownership, and capacity building demonstrate higher social cohesion and more durable economic benefits. Moreover, integrating participatory evaluation tools within project cycles increases transparency, accountability, and community trust. The study contributes to the field of sustainable development by providing a replicable and adaptable impact assessment model applicable across diverse socio-economic contexts. This framework not only guides policymakers and practitioners in designing more effective community engagement programs but also ensures that interventions generate measurable and sustainable outcomes for all stakeholders involved.